2015
DOI: 10.1371/journal.pone.0113261
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Crop Diversity Mitigates Weather Variations and Improves Yield Stability

Abstract: Cropping sequence diversification provides a systems approach to reduce yield variations and improve resilience to multiple environmental stresses. Yield advantages of more diverse crop rotations and their synergistic effects with reduced tillage are well documented, but few studies have quantified the impact of these management practices on yields and their stability when soil moisture is limiting or in excess. Using yield and weather data obtained from a 31-year long term rotation and tillage trial in Ontari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
199
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(214 citation statements)
references
References 91 publications
11
199
1
3
Order By: Relevance
“…In rainfed agriculture, lower water productivity for CC was reported compared with other rotations (Copeland et al, 1993;Varvel, 1994;Pikul et al, 2012). Studies available on crop rotations in limited and full irrigation conditions show a similar result to the present paper, that is, less or similar impact of rotation compared with continuous cropping in yield and resource use (Schneekloth et al, 1991;Gaudin et al, 2015). Holling (1973) defined a resilient system as a system that retains its productivity following a perturbation (drought, disease, pest…).…”
Section: Economic Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…In rainfed agriculture, lower water productivity for CC was reported compared with other rotations (Copeland et al, 1993;Varvel, 1994;Pikul et al, 2012). Studies available on crop rotations in limited and full irrigation conditions show a similar result to the present paper, that is, less or similar impact of rotation compared with continuous cropping in yield and resource use (Schneekloth et al, 1991;Gaudin et al, 2015). Holling (1973) defined a resilient system as a system that retains its productivity following a perturbation (drought, disease, pest…).…”
Section: Economic Analysissupporting
confidence: 80%
“…Holling (1973) defined a resilient system as a system that retains its productivity following a perturbation (drought, disease, pest…). Crop diversity was, therefore, suggested as a big contributor to increasing a cropping systems resilience (Lin, 2011;Gaudin et al, 2015). Water limitation is among the main factors that challenge a systems resilience.…”
Section: Economic Analysismentioning
confidence: 99%
“…Furthermore, crop rotations with a higher share of cereals show a negative impact on yield stability of winter wheat, especially for wheat monocultures. In contrast, diverse crop rotations with favorable preceding crops (e.g., legumes) affect the yield stability of the main crop winter wheat positively [15][16][17][18][19]. Beyond that, cultivar choice is an effective tool in farming practice, which is used to support yield stable wheat production [3,12,20].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, our results suggest that further investment in research into diversification techniques has the potential to improve productivity of sustainable agricultural methods to equal conventional yields. Encouragingly, the few long-term studies that have been conducted have demonstrated that diversification techniques enhance yields while enhancing ecosystem services, profitability and stability [18,23,[32][33][34][35].…”
mentioning
confidence: 99%